EXAMINING GEN Z CONSUMERS’ PURCHASE INTENTION TOWARDS ORGANIC FOOD IN COIMBATORE CITY - R, Kavipriya; T, Kumarasamy; T. S., Sreenidhi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Changing consumer attitudes and a growing awareness of health and environmental concerns are driving significant growth in the organic food industry in India. This change is especially evident among Generation Z, who are becoming more conscious of how their consumption affects the planet. The COVID-19 pandemic has further accelerated this movement, leading consumers to adopt healthier and more sustainable eating practices. In Coimbatore City, the popularity of organic food is increasing, this study investigates the factors that shape Gen Z consumers' intentions to buy organic products. A structured questionnaire was distributed to 219 Gen Z participants, focusing on aspects such as health awareness, environmental concerns, product quality, price sensitivity, and social influences. Structural Equation Modeling (SEM) was used to analyze the data, Factor Analysis, and One-Way ANOVA. The results indicate that regular buyers of organic food demonstrate stronger intentions to purchase, with health benefits, environmental sustainability, and perceived product quality being significant motivators. While organic products are well-known, the decisions to purchase are greatly impacted by the prices and social influences despite the awareness. The analysis also reveals no significant links between demographic factors like age, education, and income, and purchase intentions, suggesting that Gen Z consumers from various backgrounds have similar reasons for opting for organic food. These results highlight the increasing popularity of conscious consumption among Gen Z and provide important insights for stakeholders looking to engage with the expanding organic food industry in Coimbatore.